RENAL PELVIC CALCULUS CO-EXISTING WITH AN ABERRANT RENAL VESSEL: CASE REPORT AND LITERATURE REVIEW - A Abdulkadir (Ntec Specialist, 2018)
Introduction: Appraisals on the pair of renal pelvic calculus with an aberrant renal vessel that causes urinary tract obstruction as synchronous renal lesions are rare. Separately, either can give rise to flank pain; but the lesion that is distinct on abdominal ultrasound scan and intravenous urography is calculus. The aberrant vessel often turns out an ulterior component of the combination. During surgery, when unnoticed this may result in vascular injury or persistent extrinsic ureteral obstruction. Case report: The patient was a 19-year-old male pupil who had the right recurrent flank pain that worsened over time. His abdominopelvic ultrasound scan and intravenous urography revealed right renal pelvic calculus with features of chronic kidney disease. The results of his urine microscopy, culture and sensitivity; urea, electrolytes and creatinine; full blood count and differentials were normal. He consented to an open right renal exploration. Intraoperatively, an aberrant renal vessel to the lower pole of the right kidney crossed the posterior proximal third of the ureter. The ipsilateral kidney was shrunken and had peri-renal fibrosis. The contralateral kidney was normal. He had pyelolithotomy with dismembering of the ureter at the site of obstruction which was anastomosed to reposition the ureter posterior to the aberrant vessel. His postoperative recovery was uneventful. He had no flank pain, and Doppler ultrasound displayed good bilateral renal perfusions at follow up. Conclusion: The diagnosis of an aberrant renal vessel causing a ureteral obstruction that coexists with renal Pelvic Calculus requires a high index of suspicion. Identifying this amalgam is essential to the management that will focus on the lesions and circumvent complications.